Biomarkers of vascular cognitive impairment - O. V. Zimnitskaya; E. Yu. Mozheyko; M. M. Petrova (Кардиоваскулярная терапия и профилактика, 2021)
There is currently no approved list of vascular cognitive impairment biomarkers. The main problem for the practitioner in identifying cognitive impairment in patients is the differential diagnosis of Alzheimer's disease, vascular cognitive impairment, and other diseases, which are much less common. Vascular cognitive impairment includes post-stroke dementia, cognitive dysfunction in cardio-and cerebrovascular diseases. Without etiology identification, it is impossible to prescribe adequate treatment. Another challenge is identifying cognitive impairment before dementia develops. This literature review is devoted to the search and critical analysis of candidates for biomarkers of vascular cognitive impairment and the establishment of markers of moderate cognitive dysfunction. The papers were searched for in the Web of Science and PubMed databases. A list of cerebrospinal fluid, plasma, serum and genetic biomarkers was made, allowing for differential diagnosis between vascular impairment and Alzheimer's disease. The markers of moderate cognitive dysfunction, which make it possible to identify cognitive impairment at the pre-dementia stage, were also identified.